Pengaruh Real-Time Interactivity Live Streaming Terhadap Impulse Buying Yang Dimediasi Oleh Perceived Enjoyment Dan FOMO Pada Gen_Z - Aloysius Timoty; Alexander Mario Retto Djong (Jurnal Minfo Polgan, 2026)
This study aims to examine the effect of real-time interactivity in Shopee live streaming on impulse buying behavior among Generation Z in Karanganyar Regency, with perceived enjoyment and the feeling of being left out of the moment or Fear of Missing Out (FoMO) as mediating variables. Grounded in the Stimulus–Organism–Response (S-O-R) theory, real-time interactivity in live streaming functions as the stimulus, perceived enjoyment and FoMO represent internal psychological responses (organism), and impulse buying serves as the behavioral response. A survey-oriented quantitative method was employed to collect data from respondents through structured questionnaires. distributed to Generation Z consumers actively using Shopee Live in Karanganyar Regency. Data were examined through the PLS-SEM approach using SmartPLS 4, showing that real-time interactivity has a significant positive relationship with perceived enjoyment. (β=0.675, p<0.001) and FoMO (β=0.310, p=0.001), while perceived enjoyment (β=0.363, p=0.001) and FoMO (β=0.586, p<0.001) each positively and significantly influence impulse buying. The direct effect of real-time interactivity on impulse buying was not significant (β=−0.145, p=0.070), confirming full mediation through both psychological pathways. The model explains 61% of impulse buying variance (R²=0.610). This study contributes theoretically by extending the S-O-R framework through a parallel mediation model and provides practical implications for e-commerce platforms and SMEs in designing more effective and consumer-oriented live streaming strategies.